UPAYA KEPALA SEKOLAH UNTUK MENINGKATKAN PROFESIONALISME GURU MELALUI SUPERVISI KEGIATAN BELAJAR MENGAJAR DI SD - Farida Hastuti (UNIVERSITAS BENGKULU, 2017)
managerial principals is the ability or skill shown by schools in organizing and utilizing all components or areas of arable school . The ability to grow through the coaching process and supported by factors that influence and melatar tow. As for the factors that affect a person's level of ability is an element of maturity , with regard to the knowledge and skills gained from education, training and experience. in the implementation of managerial principals in this teacher , found a positive influence on the creation of the professionalism of teachers in learning activities , it is marked by a significant increase in each cycle , cycle 1 and cycle amounted to 56.9 % 2 94.5 % . it demonstrates the success of managerial leadership to the school head teacher professionalism.